Pengaruh Kepemimpinan, Kompetensi dan Kompensasi terhadap Prestasi Kerja Karyawan PT. Kelindo Bogor - Ade Kurniawan; Sri Harini; Palahudin Palahudin (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Research aimed at examining the impact of leadership, competence and compensation on work performance at PT. Kelindo. The research method is quantitative descriptive and verification, involving 38 respondents through distributing questionnaires. Data were analyzed using an ordinal scale through multiple regression analysis and hypothesis testing. The results show that employee responses to leadership are quite good, competence is high, competence is quite capable, and work performance is quite high. Simultaneously and partially, leadership, competence, and failure have a significant positive impact on work performance. These findings illustrate that increased employee performance can be encouraged through effective leadership, appropriate competencies and fair increases, and can be used as material for strategic consideration in HR development at PT. Kelindo.